FORESTRY EXTENSION WORKERS' COMMUNICATION STRATEGIES IN INCREASING FOREST FARMERS' GROUP PARTICIPATION (KTH) IN THE CENTRAL KALIMANTAN PROVINCE FORESTRY SERVICE /UPT KPHP BARITO TENGAH IN NORTH BARITO REGENCY - Aquarini; Bambang Rudianto (RADJA PUBLIKA, 2025)
Community participation is a crucial factor in the success of sustainable forest management, particularly within the framework of social forestry. Forest Farmer Groups (Kelompok Tani Hutan/KTH), as key actors at the site level, require effective facilitation to actively engage in forest management activities. In this context, forestry extension officers play a strategic role as intermediaries between government policies and local communities. This study aims to analyze the communication strategies employed by forestry extension officers to enhance the participation of Forest Farmer Groups at the Forestry Service of Central Kalimantan Province through the Barito Tengah Forest Management Unit (UPT KPHP Barito Tengah) in North Barito Regency. This research adopts a qualitative approach using in-depth interviews with forestry extension officers as research informants. The data were analyzed descriptively through thematic categorization focusing on the role of extension officers, communication methods and media, socio-cultural adaptation, dialogic interaction, and communication barriers in forestry extension activities. The findings indicate that the communication strategies applied by forestry extension officers are persuasive, participatory, and context-based. Interpersonal communication through face-to-face interactions and field-based mentoring is prioritized, while communication styles are adjusted to local social and cultural conditions. Two-way dialogue and discussion facilitate a process of meaning construction between extension officers and Forest Farmer Group members, leading to improved understanding, motivation, and behavioral change in forest management practices. These communication strategies contribute positively to increasing the participation of Forest Farmer Groups and support the implementation of social forestry policies as well as sustainable forest management objectives.